Hydrochemistry and trophic state change in a large reservoir in the Brazilian northeast region under intense drought conditions - Santos, J. A. (2017)
The study shows changes on physical and chemical water parameters and of trophic state in a large reservoir in the Brazilian semiarid region following decreasing reservoir volume due to rainfall shortage during four consecutive years. The monitoring period, between November 2011 and May 2014, assessed approximately 50% water volume reduction and 10 meters’ decrease of reservoir water level that degraded water quality. Decrease in reservoir volume, strong evaporation and the permanent influence of anthropogenic activities, favored the concentration of salts and accumulation of nutrients and of increasing pH. Thermal stratification of the water column occurred when volume was maximum and lead to a significant reduction in dissolved oxygen in the hypolimnion (0.07 to 2.62 mg L–1). Diminishing volume resulted in mixing of the hypolimnion nutrient-rich and oxygen-poor waters in the entre water column and changed the initial oligotrophic condition to eutrophic. However, the temporal scale of the response of the reservoir’s trophic state differs in the different areas of the reservoir. Whereas deeper areas accumulating nutrients from aquaculture and agriculture progressively became mesotrophic and eventually eutrophic; shallower regions far from direct anthropogenic influences, changed their trophic sate much later, but rapidly turned into super-eutrophic conditions, probably due to more intense sediment resuspension and water mixing. Trophic State Index followed nutrient increase during most of the period. However, it also responded to an increase in chlorophyll a concentrations when the reservoir achieved its minimum volume, in particular in the shallower areas. The results suggest that this type of reservoir systems are vulnerable to eutrophication during extended drought periods and that a better assessment of the maximum support capacity for reservoir activities, particularly aquaculture, must be re-assessed taking into consideration worst case scenarios forecasted by global climate change.